Adaptation and validation of antibody-ELISA using dried blood spots on filter paper for epidemiological surveys of tsetse-transmitted trypanosomosis in cattle - Hopkins, J.S.; Chitambo, H.; Machila, N.; Luckins, A.G.; Rae, P.F.; Bossche, P. van den; Eisler, M.C. (1998)
The indirect enzyme-linked immunosorbent assay (ELISA) for the detection of anti-trypanosomal antibodies in bovine serum was adapted for use with dried blood spots on filter paper. Aborbance (450 nm) results for samples were expressed as percent positivity, i.e., percentage of the median absorbance result of four replicates of the strong positive control serum. The antibody-ELISA was evaluated in Zambia for use in epidemiological surveys of the prevalence of tsetse-transmitted bovine trypanosomosis. Known negative sample (sera, n=209; blood spots, n=466) were obtained from cattle from closed herds in tsetse-free areas close to Lusaka. Known positive samples (sera n=367; blood spots n=278) were obtained from cattle in Zambia's Central, Lusaka and Eastern Provinces, diagnosed as being infected with Trypanosoma brucei, T. congolense or T. vivax using the phase-contrast buffy-coat technique or Giemsa-stained thick and thin blood smears. For sera (at a cut-off value of 23.0 percent positivity) sensitivity and specificity were 86.1 and 95.2 percent respectively. For bloodspots (at a cut-off value) of 18.8 percent positivity) sensitivity and specificity were 96.8 and 95.7 percent respectively. The implications of persistence of antibodies following treatment or self-cure are discussed.